2011
DOI: 10.1094/mpmi-09-10-0220
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Lotus japonicus Subtilase Gene During Arbuscular Mycorrhiza Is Dependent on the Common Symbiosis Genes and Two cis-Active Promoter Regions

Abstract: The subtilisin-like serine protease SbtM1 is strongly and specifically induced during arbuscular mycorrhiza (AM) symbiosis in Lotus japonicus. Another subtilase gene, SbtS, is induced during early stages of nodulation and AM. Transcript profiling in plant symbiosis mutants revealed that the AM-induced expression of SbtM1 and the gene family members SbtM3 and SbtM4 is dependent on the common symbiosis pathway, whereas an independent pathway contributes to the activation of SbtS. We used the specific spatial exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…FDR-corrected P values (FDR-P) are indicated. References for the AM-induced genes identified are as follows: MtPt4 (Javot et al, 2007), MtMyb1 (Liu et al, 2003), MtTi1 (Grunwald et al, 2004), MtLec7 (Frenzel et al, 2005), MtGst1 (Wulf et al, 2003), MtBcp1 (Hohnjec et al, 2005), MtLec5 (Frenzel et al, 2005), MtGlp1 , MtHa1 (Krajinski et al, 2002), MtScp1 (Liu et al, 2003), MtVapyrin (Pumplin et al, 2010), MtSbtM1 (Takeda et al, 2011), MtZip7 (Burleigh et al, 2003), MtAnn2 , and MtDxs2 (Floss et al, 2008 roots (Liu et al, 2003;Wulf et al, 2003;Hohnjec et al, 2006;Kü ster et al, 2007b;Guether et al, 2009). Interestingly, the categories membrane transporters, signaling, and TFs were not only prominent but their members were also expressed most significantly different from others in AM roots (data not shown), based on statistical analyses implemented in MapMan (Usadel et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…FDR-corrected P values (FDR-P) are indicated. References for the AM-induced genes identified are as follows: MtPt4 (Javot et al, 2007), MtMyb1 (Liu et al, 2003), MtTi1 (Grunwald et al, 2004), MtLec7 (Frenzel et al, 2005), MtGst1 (Wulf et al, 2003), MtBcp1 (Hohnjec et al, 2005), MtLec5 (Frenzel et al, 2005), MtGlp1 , MtHa1 (Krajinski et al, 2002), MtScp1 (Liu et al, 2003), MtVapyrin (Pumplin et al, 2010), MtSbtM1 (Takeda et al, 2011), MtZip7 (Burleigh et al, 2003), MtAnn2 , and MtDxs2 (Floss et al, 2008 roots (Liu et al, 2003;Wulf et al, 2003;Hohnjec et al, 2006;Kü ster et al, 2007b;Guether et al, 2009). Interestingly, the categories membrane transporters, signaling, and TFs were not only prominent but their members were also expressed most significantly different from others in AM roots (data not shown), based on statistical analyses implemented in MapMan (Usadel et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The GOF-CCaMK variants were introduced into wild-type plants to examine AMS-specific gene expression ( Figure 1A). The expression analysis revealed that all of the kinase-only GOF-CCaMK variants except for the NES fusion could induce expression of SbtM1 but not that of PT4, whereas full-length CCaMK TD and snf1 could not induce expression of either gene ( Figure 1A; Takeda et al, 2011). Because SbtM1 is involved in an early stage of AM fungal colonization ), these results showed that kinase-only GOF-CCaMK could activate the early signaling pathway in AMS.…”
Section: Nuclear Localization Of Deregulated Ccamk Strongly Induced Bmentioning
confidence: 90%
“…Whereas SbtM4 expression is maintained throughout nodule development, SbtS expression is induced only in the early stage of nodule development and is hardly detected in nodules. In snf1 mutants, SbtM4 expression is observed only in the late stage of SPN formation, whereas SbtS is not detected (Takeda et al, 2011). These facts indicate that RNS responses are not fully activated in snf1.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…). CSSP‐independent AM or Myc‐LCO‐induced gene regulation changes were previously observed in M. truncatula (Czaja et al ., ), in L. japonicus (Kistner et al ., ; Takeda et al ., ) and in rice (Gutjahr et al ., ; Mukherjee & Ané, ). One early event that does not require DMI3 is nuclear movement towards the site of fungal contact on the root surface (Genre et al ., ).…”
Section: Discussionmentioning
confidence: 99%